2000
DOI: 10.1897/1551-5028(2000)019<0293:efoned>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Fate of Nonylphenol Ethoxylates: Differential Adsorption of Homologs to Components of River Sediment

Abstract: Abstract-Nonylphenol ethoxylate (NPEO x ) homologs present in commercial mixtures were rapidly adsorbed to and desorbed from native river sediment. Adsorption isotherms, established using high-performance liquid chromatography analysis to monitor individual homologs NPEO 3 to NPEO 13 simultaneously, were linear for each component adsorbing to native sediment, organic-free sediment, and kaolinite, usually with small positive intercepts on the isotherms indicating an additional low-capacity, high-affinity bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Since the sedimentary organic carbon is an important factor in the sorption of EDCs (John et al, 2000;Ferguson et al, 2001), the influence of the total organic carbon (TOC) on the distribution of APs and other estrogens in our surface sediments was investigated using linear regression analysis conducted by the software of Origin 8. It was found that OP, NP and E2 were significantly correlated with TOC contents and their correlation coefficients (r) were 0.83, 0.82 and 0.90 (Fig.…”
Section: Correlations Of Edcs With Sedimentary Organic Carbonmentioning
confidence: 99%
“…Since the sedimentary organic carbon is an important factor in the sorption of EDCs (John et al, 2000;Ferguson et al, 2001), the influence of the total organic carbon (TOC) on the distribution of APs and other estrogens in our surface sediments was investigated using linear regression analysis conducted by the software of Origin 8. It was found that OP, NP and E2 were significantly correlated with TOC contents and their correlation coefficients (r) were 0.83, 0.82 and 0.90 (Fig.…”
Section: Correlations Of Edcs With Sedimentary Organic Carbonmentioning
confidence: 99%
“…Nonylphenoxyethoxy acetic acid was shown to be the most important carboxylate species. John et al [24] found that NPE homologues, commonly present in commercial mixtures, were rapidly adsorbed to and desorbed from native river sediment. The adsorption partition coefficients (Kd) for the native sediment decreased progressively according the chain length of alkyl moiety from 1460 L kg-1 for NPE3 to 450 L kg-1 for NPE10.…”
Section: Environmental Fate Of Nonylphenol and Derivatesmentioning
confidence: 99%
“…Due to their lipophilic properties, these degradation products sorb and concentrate during wastewater treatment to the organic particles or mineral constituent present. Sorption has been shown to be highly dependent on the number of ethoxy groups [3,[10][11][12]. Compounds such as NP may pose a health * To whom correspondence may be addressed (gerda@rh.dk).…”
Section: Introductionmentioning
confidence: 99%